Unveiling the Bioactive Compound Potential of Red Mariposa Christia vespertilionis Using Chemometric and ATR-FTIR Spectroscopy - Mohamad Tahier, Soraya Shafawati; Jaafar, Nurfirzana Liyana Abdul (Universitas Gadjah Mada, 2025)
Red Mariposa Christia vespertilionis (MCV) is a medicinal plant containing potential bioactive compounds of interest; however, these have not been fully investigated. This work focuses on the antioxidant properties of red MCV, as evaluated by attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy with chemometric methods of analysis such as principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA).The highest total phenolic levels (15.91 ± 0.04 mg GAE/mL) were found in the leaf of aqueous extracts, and total flavonoid content, 15.7 ± 0.04 mg QE/mL, in hexane extracts, compared to other solvents, which is linked to better DPPH radical scavenging activity (74.24 ± 0.00%). The FTIR spectra demonstrated the presence of hydroxyl (O−H) and carbonyl (C=O) functional groups, indicating a significant abundance of polyphenols and flavonoids. The bioactive composition of the red MCV was definitively confirmed through chemometric techniques. The chemometric analysis revealed that methanol and aqueous extracts offer maximum antioxidant and optimum solvent profiles. These results show that red MCV is a feasible source for pharmaceutical and nutraceutical applications dealing with oxidative stress.